Exploring Imam Al-Ghazali's Teachings: The Application of Mashlahah-Mursalah in Balancing Islamic Values and Digital Conduct at the Intersection - Afna, Mauloeddin (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
This study overviewed the teaching of Manhaj of Mashlaha-Mursalah as the framework for encompassing Muslims to act within digital interaction. The paper aimed to provide insights into digital behavior by examining the relevance of the Al Ghazali approach, the Qiyas, to synthesize husnul hulq teaching to become the framework which properly taken in a contemporary context. They employed a qualitative approach by acquiring the literature review of Al Gazali's work, i.e., Ihya Ulummuddin, as the main framework to be the foundation to be exposure to Indonesian digital behaviors, managing a social media image with massive information, and digesting reaction with hoaxes. The paper presented the finding of analysis, which indicated the teaching offered valuable insight and holistic for three core lessons, i.e., The cores are as follow; (1). The principles of the manhaj on social media manners, (2). The navigation frameworks of Manhaj, and (3). The Manhaj Objectives for Digital World. Therefore, by synthesizing these three cores, the writer concluded that the legal standing, Manhaj, should concern Husnul Hulq, authenticity, sincerity, and Rahmatan lil-Alamin as the framework to foster social media etiquette that aligns with Islamic values.